(untitled) (LACCEI, 2024)
Nowadays, Supply chains are subject to high variability due to the instability and uncertainty of the markets. Market turbulence requires a higher connection and an accelerated reconfiguration of their productive capacities. That implies rapid changes and cost-effectiveness in response to demand change. Therefore, this paper explores the role of reconfigurability SC as a driver of SC performance. This deductive research aims to evaluate the effect of each reconfigurability dimension on SC performance and analyze the sectors that show higher manufacturing reconfigurability processes levels. We hypothesize that there is a positive and significant relationship between reconfigurability aimed at reducing time and effort in the SC performance. By employing the hierarchical regression analysis on the HPM survey database on a sample of 309 manufacturing Plants, we find that some reconfigurability dimensions explain at least 15% of SC performance, at the time, we find some companies prefer to improve reconfigurability dimension that directly impacts on manufacturing cost than dimension that requires restructure machinery and layout to diminish lead time, due the cost, time, interface, and other issues required